On some strange similarities: classical component in Annenskyi’s and Dario’s works - Шелогурова, Галина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
The works by Annenskyi and Dario were never compared. It seems obvious that they have little in common, but the ways the poets apprehend Greek culture share a few features. In their attempts to find the most acceptable variant to unite antiquity and modern literature and art, we see great influence of the ideas and poetry of Lecont de Lisle.